2016
DOI: 10.1111/febs.13698
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase: a cellular energy sensor that comes in 12 flavours

Abstract: The AMP‐activated protein kinase (AMPK) is a sensor of cellular energy status that is expressed in essentially all eukaryotic cells, suggesting that it arose during early eukaryotic evolution. It occurs universally as heterotrimeric complexes containing catalytic α subunits and regulatory β and γ subunits. Although Drosophila melanogaster contains single genes encoding each subunit, in mammals, each subunit exists as multiple isoforms encoded by distinct genes, giving rise to up to 12 heterotrimeric combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
309
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 325 publications
(312 citation statements)
references
References 83 publications
(139 reference statements)
1
309
0
2
Order By: Relevance
“…Taken together, these results suggest that while AMPK-α2 might indeed be a tumor suppressor, AMPK-α1 might be an oncoprotein that promotes the survival of tumor cells, possibly by protecting them under conditions of energy stress. Consistent with this, recent analyses of the human cancer genome databases revealed that while the PRKAA2 gene (encoding α2) is quite often mutated in human cancers, PRKAA1 tends to be amplified instead (Monteverde et al, 2015;Ross et al, 2016). Vila et al (2017) were interested in the role of UBE2O, a large ubiquitin ligase with both E2 and E3 activities.…”
Section: Grahame Hardiementioning
confidence: 85%
See 2 more Smart Citations
“…Taken together, these results suggest that while AMPK-α2 might indeed be a tumor suppressor, AMPK-α1 might be an oncoprotein that promotes the survival of tumor cells, possibly by protecting them under conditions of energy stress. Consistent with this, recent analyses of the human cancer genome databases revealed that while the PRKAA2 gene (encoding α2) is quite often mutated in human cancers, PRKAA1 tends to be amplified instead (Monteverde et al, 2015;Ross et al, 2016). Vila et al (2017) were interested in the role of UBE2O, a large ubiquitin ligase with both E2 and E3 activities.…”
Section: Grahame Hardiementioning
confidence: 85%
“…AMP-activated protein kinase (AMPK) is a cellular energy sensor involved in matching the supply of ATP from catabolism to the demand created by anabolism and other ATP-consuming activities, including cell division (Ross et al, 2016). As soon as demand out-strips supply the ADP:ATP ratio will increase, and this is amplified by the adenylate kinase reaction (2ADP ↔ ATP + AMP) into even larger increases in AMP:ATP ratios.…”
Section: Grahame Hardiementioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the in vivo importance of other AMPK subunits in combination with genetic loss of tumor‐suppressing pathways has not been studied. However, this is important given that the 12 different AMPK heterotrimer combinations have unique tissue‐specific expression, enzyme activities, and substrates (Ross et al ., 2016) and may have differential effects in distinct settings of oncogenesis (i.e., when interacting with distinct tumor‐promoting pathways).…”
Section: Introductionmentioning
confidence: 99%
“…Each occurs as multiple isoforms (α1/α2, β1/β2, γ1/γ2/γ3), generating up to twelve possible combinations (1). Repeated sequences in the γ subunits generate three binding sites for the regulatory nucleotides AMP, ADP and ATP, and some AMPK activators (e.g.…”
mentioning
confidence: 99%